Ālūra Veṅkaṭarāv - Huyilagōḷa, Varadarāja (Sāhitya Akādemi, 1998)
On the brief life and works of Alūra Veṅkaṭarāva, 1880-1964, Kannada scholar
Includes bibliographical references. - Kannada in kanares. Schr.
Keywords: Biografie; Veṅkaṭarāva; Ālūra 1880-1964; Veṅkaṭarāva; Ālūra; Authors; Kannada / Biography / India / Andhra Pradesh